1999
DOI: 10.1063/1.125071
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of Ba0.5Sr0.5TiO3 thin films on LaAlO3

Abstract: Perovskite barium strontium titanate Ba0.5Sr0.5TiO3(BST) thin films were grown on (001) LaAlO3 (LAO) using pulsed-laser ablation. The microstructures of the as-grown BST films were studied with selected electron diffraction, transmission electron microscopy, and scanning transmission electron microscopy. The BST thin films are oriented with their [001] directions parallel to the 〈102〉 directions of the LAO. Both cross-sectional and plan-view studies show the BST films to be single crystals with smooth surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Such strain energy also makes it difficult to grow high-quality epitaxial BST films on MgO substrates. Chen et al 56,57 and Gao et al 58 have examined the interface behavior of the epitaxial (Ba 0.6 Sr 0.4 )TiO 3 films on the (001) MgO and (001) LAO substrates by using x-ray diffraction and electron microscopy. Their results showed that the asgrown film has a high degree of crystallinity and good in-plane orientation: <100> BST //<100> MgO and (100) BST //(100) MgO , as confirmed by x-ray diffraction and selected-area electron diffraction patterns.…”
Section: Interfacial Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Such strain energy also makes it difficult to grow high-quality epitaxial BST films on MgO substrates. Chen et al 56,57 and Gao et al 58 have examined the interface behavior of the epitaxial (Ba 0.6 Sr 0.4 )TiO 3 films on the (001) MgO and (001) LAO substrates by using x-ray diffraction and electron microscopy. Their results showed that the asgrown film has a high degree of crystallinity and good in-plane orientation: <100> BST //<100> MgO and (100) BST //(100) MgO , as confirmed by x-ray diffraction and selected-area electron diffraction patterns.…”
Section: Interfacial Structuresmentioning
confidence: 99%
“…Similar anti-domain structures were also observed in the (Ba 0.6 Sr 0.4 )TiO 3 films on (001) LAO. 58 Because plenty of twins exist in the LAO substrate surface, they are beneficial to releasing the strain energy between the BST film and the LAO, so that the total energy in this system can be reduced during film growth. Consequently, it is relatively easier to grow highquality epitaxial BST films on LAO than on MgO.…”
Section: Interfacial Structuresmentioning
confidence: 99%
“…Accordingly, the interfacial layer should be further studied in order to achieve the applications of the BST thin film capacitors. Although, many works were done to investigate the influences of interfacial layer on the thin film deposition method, film thickness, annealing, buffer layer, micostructure, electrode deposition [15][16][17][18][19][20]. Unfortunately, the effects of interfacial layer on dielectric properties of BST thin films have less been reported.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the FWHM values of BST thin films grown on MgO substrates and LAO substrates are around 0.54 and 0.15 , respectively. 15,16 At room temperature, the lattice parameters for the bulk BST are a ¼ b ¼ c ¼ 3.965 Å . 6 Calculation based on Figure 1(a) results in c-axis lattice constants of 3.992 Å and 5.653 Å for BST thin film and GaAs substrate, respectively.…”
Section: Methodsmentioning
confidence: 99%